Experimental signatures of fermiophobic Higgs bosons - Brucher, L. (2014)
The most general Two Higgs Doublet Model potential without explicit CP violation depends on 10 real independent parameters. Excluding spontaneous CP violation results in two 7 parameter models. Although both models give rise to 5 scalar particles and 2 mixing angles, the resulting phenomenology of the scalar sectors is different. If flavour changing neutral currents at tree level are to be avoided, one has, in both cases, four alternative ways of introducing the fermion couplings. In one of these models the mixing angle of the CP even sector can be chosen in such a way that the fermion couplings to the lightest scalar Higgs boson vanishes. At the same time it is possible to suppress the fermion couplings to the charged and pseudo-scalar Higgs bosons by appropriately choosing the mixing angle of the CP odd sector. We investigate the phenomenology of both models in the fermiophobic limit and present the different branching ratios for the decays of the scalar particles. We use the present experimental results from the LEP collider to constrain the models.